Abordagens da Controladoria nos Trabalhos do Congresso USP de Controladoria e Contabilidade: Um Enfoque nas Perspectivas Conceitual, Procedimental e Organizacional - Ilse Maria Beuren; Juliana Pinto; Vinícius Costa da Silva Zonatto (Revista Contemporânea de Contabilidade, 2012)
The study identifies the approach of comptrollership on papers published in the annals of the USP Congress on Comptrollership and Accounting from 2001 to 2006, based on documentary research and descriptive denotation. The results show that in the conceptual perspective there is no concern in defining the term comptrollership and neither its relationship with other areas of knowledge. In the procedural perspective, there is no consensus about the typical activities but it stands out the one related to information systems. In the organizational perspective, the comptrollership is not seen as a formally established organizational unit with power of decision, but as an administrative unit that supports the decision-making.